THE RELATIONSHIP BETWEEN THE BALANCED SCORECARD AND THE COBIT-5 CRITERION IN IMPROVING BANKING PERFORMANCE, AN APPLIED RESEARCH IN A SAMPLE OF COMMERCIAL BANKS LISTED IN THE IRAQI STOCK EXCHANGE - Waad Hadi Abd; Duha Alwan Kazem (Scholar Express Journals, 2022)
Research aims to me Provide an introductory framework on the concepts of the balanced scorecard and its dimensions and how to employ them, withstandardcobit-5 and its reflection on improving banking performance .and how Using the balanced scorecard according to standardcobit-5 related to banks, on a sample Of the Iraqi commercial banks (Bank of Baghdad, Ashur International Bank, Trans-Iraq Bank)in order to Know the relationship between the balanced scorecard andccbit-5toDetermining the strengths in the performance and maintaining them continuously in the long term, and identifying the shortcomings and weaknesses in the banking performance and avoiding them in the near future The research reached a set of conclusions, the most important of which is The weakness of the study sample banks in achieving high percentages in the index The suitability of the objectives of information technology systems, although there is a slight advantage to the Ashur Bank, since Use of technology by banks in support of his business efficiency and competitive comparison with size Advances in technology and information that are used by other competing banks, this research recommends The necessity for all the banks of the study sample to improve the indicator of the extent to which the objectives of the technological information systems are appropriate because the use of technological techniques by the banks contributes to supporting their business and thus increases the efficiency in banking business
Keywords: Words; Balanced Score Card; COBAIT; indicator